Transformation of Digital Strategy in The E-Commerce Ecosystem: The Role of Digital Literacy as a Moderator of Shopee Users' Purchase Decisions in Indonesia - Harisuddin; Muhammad Junaid Kamaruddin (Journal of Business and Behavioural Entrepreneurship, 2026)
In Indonesia's fiercely competitive e-commerce market, strategies need to be modified to take customers' cognitive capacities and feature complexity into consideration. This study attempts to assess how Shopee customers' purchasing decisions are influenced by digital business models, digital innovation, and digital marketing capabilities, with digital literacy serving as a moderating variable. Purposive sampling was used to gather data from 100 active Shopee users in an explanatory quantitative approach. Variance-based Structural Equation Modeling (SEM) utilizing SmartPLS 4 software was used to evaluate the data. The results of the study show that purchasing decisions are greatly improved by digital innovation and digital business models. Nonetheless, an instance was found in which digital marketing capabilities have no discernible direct impact; this implies that consumers can view promotional content as redundant or oversaturated. This study's originality shows that digital literacy is an essential mediator that can increase the efficacy of digital tactics. The findings indicate that Shopee should change its emphasis from aggressive promotion to user education about features and cybersecurity in order to boost long-term sales conversions.